2016
DOI: 10.1007/978-1-4939-3356-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotropism: Analysis of the Root Response to a Moisture Gradient

Abstract: Running title: Hydrotropic root response to a moisture gradient 2 SummaryHydrotropism is a genuine response of roots to a moisture gradient to avoid drought. An experimental system for the induction of hydrotropic root response in Petri dishes was designed by pioneering groups in the field. This system uses split agar plates containing an osmolyte only in a region of the plate in order to generate a water potential gradient.Arabidopsis seedlings are placed on the MS agar plate so that their root tips are near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…To test the effect of Ca 2+ on the root’s tropic response to moisture distribution, we treated wild-type (Col-0) plants with the highly selective, cell-permeant Ca 2+ chelator 1,2-bis(2-aminophenoxy)ethane- N , N , N′ , N′ -tetraacetic acid tetrakis–acetoxymethyl ester (BAPTA-AM) before hydrostimulation using the split-agar/sorbitol system. Control plants (without BAPTA-AM) displayed normal root bending, as described in a similar published experimental setup ( 13 , 33 , 34 ), whereas BAPTA-AM–treated roots displayed arrested bending in response to the change in water potential in their microenvironment even after 12 h, while continuing their growth toward the sorbitol-containing media ( Fig. 4 A and B ).…”
Section: Resultssupporting
confidence: 70%
“…To test the effect of Ca 2+ on the root’s tropic response to moisture distribution, we treated wild-type (Col-0) plants with the highly selective, cell-permeant Ca 2+ chelator 1,2-bis(2-aminophenoxy)ethane- N , N , N′ , N′ -tetraacetic acid tetrakis–acetoxymethyl ester (BAPTA-AM) before hydrostimulation using the split-agar/sorbitol system. Control plants (without BAPTA-AM) displayed normal root bending, as described in a similar published experimental setup ( 13 , 33 , 34 ), whereas BAPTA-AM–treated roots displayed arrested bending in response to the change in water potential in their microenvironment even after 12 h, while continuing their growth toward the sorbitol-containing media ( Fig. 4 A and B ).…”
Section: Resultssupporting
confidence: 70%
“…S1a-c). 12,13,15,[22][23][24] We found that in wild-type Col-0 seedlings, the lower water potential side of the roots contain more actively dividing cells and more meristematic cortex cells compared to the higher water potential side ( Fig. 1a, b, e, Supplementary information, Fig.…”
Section: Resultsmentioning
confidence: 92%
“…S1 using 4-day-old seedlings in a split-agar system modified from previously reports. 22,24 We added 200 mM D-sorbitol at the bottom right side of the Petri dish if the roots were used for propidium iodide staining after hydrostimulation treatment. In other experiments, 800 mM D-sorbitol was used.…”
Section: Methodsmentioning
confidence: 99%
“…Antoni etal . [17] and Shkolnik etal . [22] modified the split-agar/sorbitol system of Takahashi etal .…”
Section: Introductionmentioning
confidence: 98%
“…Despite water sensing being the subject of very early plant physiology studies, until recently the mechanisms of this growth response wereessentially unknown. Phenotyping and screening procedures in model plant and crop species are needed for genetic dissection of complex biological processes such as hydrotropism [16,17]. Therefore, an easier protocol that allows the analysis of the hydrotropic response in Arabidopsis seedlings wouldhelp to isolate new genes implicated in this response.…”
Section: Introductionmentioning
confidence: 99%